1999
DOI: 10.1007/s005350050249
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of and liver injury by TT virus in patients on maintenance hemodialysis

Abstract: To study the prevalence and clinical significance of TT virus (TTV) infection in hemodialysis patients, we tested for TTV DNA in serum, using the nested polymerase chain reaction. The prevalence of TTV DNA in 352 hemodialysis patients was 32%, significantly higher than that in 50 healthy blood donors (12%). The prevalence increased with age (P = 0.0098): it was 20% (22/110) in patients aged less than 49 years, 37% (69/188) in those aged 50-69 years, and 41% (22/ 54) in those aged over 70 years. Other clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
3
23
1
Order By: Relevance
“…This was certainly instrumental in putting the new virus in the limelight, but subsequent findings have cast serious doubts on the correlation: (i) as extensively discussed above, TTV viremia is widely prevalent not only among patients with cryptogenic hepatitis but also, and at similar rates, in control groups with other forms of liver disease or no liver injury at all (8,23,35,50,66,109,170,178); (ii) when hemophiliacs and other persons with or without risk of blood-borne infections were sorted into TTV DNA-positive and -negative groups, the two groups often showed similar ALT levels (8,55,85,96,109,115,130,157,160,175); (iii) in several series of blood transfusion patients, there was no correlation between the acquisition of TTV infection and the development of hepatitis, and, in any case, the dynamics of ALT were unrelated to TTV viremia (44,59,81,96,115,147); (iv) in several studies of patients with hepatitis B or C, no correlation was found between the severity of liver damage or responsiveness to alpha interferon therapy and concomitant TTV infection (8,36,44,48,66,69,96,115,126,167); and (v) chimpanzees naturally or experimentally infected with TTV or TTV-like viruses showed no biochemical and histological signs of liver damage (106,176). Furthermore, retrospective analyses of patients treated with alpha interferon with or without ribavirin for underlying HCV ...…”
Section: Clinical Significancementioning
confidence: 91%
See 2 more Smart Citations
“…This was certainly instrumental in putting the new virus in the limelight, but subsequent findings have cast serious doubts on the correlation: (i) as extensively discussed above, TTV viremia is widely prevalent not only among patients with cryptogenic hepatitis but also, and at similar rates, in control groups with other forms of liver disease or no liver injury at all (8,23,35,50,66,109,170,178); (ii) when hemophiliacs and other persons with or without risk of blood-borne infections were sorted into TTV DNA-positive and -negative groups, the two groups often showed similar ALT levels (8,55,85,96,109,115,130,157,160,175); (iii) in several series of blood transfusion patients, there was no correlation between the acquisition of TTV infection and the development of hepatitis, and, in any case, the dynamics of ALT were unrelated to TTV viremia (44,59,81,96,115,147); (iv) in several studies of patients with hepatitis B or C, no correlation was found between the severity of liver damage or responsiveness to alpha interferon therapy and concomitant TTV infection (8,36,44,48,66,69,96,115,126,167); and (v) chimpanzees naturally or experimentally infected with TTV or TTV-like viruses showed no biochemical and histological signs of liver damage (106,176). Furthermore, retrospective analyses of patients treated with alpha interferon with or without ribavirin for underlying HCV ...…”
Section: Clinical Significancementioning
confidence: 91%
“…Although it is assumed that TTV must be highly contagious, the modes of spread are poorly understood. Most screenings have found the highest detection rates amongst polytransfused, thalassemic, long-term hemodialysis patients, hemophiliacs treated with the nonvirally inactivated clotting-factor concentrates used prior to the HIV epidemics, and intravenous drug abusers; a positive correlation often existed between the quantity of blood or blood factors received and the TTV prevalence rate (12,17,38,67,76,96,115,137,160,175), clearly indicating that TTV can behave as a transmissible blood-borne virus. Additional observations corroborating this conclusion were as follows: (i) TTV DNA was detected in commercial human plasma, clotting-factor concentrates, and intramuscular immunoglobulin (Ig) preparations (133, On the other hand, from the very beginning it was also patent that TTV viremia rates in the general population were much too high to be explained solely in terms of apparent or inapparent blood-borne transmission.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm these findings, we genetically characterized 420 clones of NG primer products from 32 thalassemia patients and 8 healthy individuals, as well as 50 PCR products amplified by TT and RD037/ 038/051/052 primers from 50 thalassemia patients and 96 TLMV-S primer product clones from 16 thalassemia patients. We detected TTV genotypes 1 to 3, 9 to 13,14,16,18,22,23, and group 5 (JT33F/JT34F/CT39F/CT44F); SENV genotypes A, B, D, and H; and four TLMV groups (three known plus one newly identified). TTV genotypes 4 to 8,15,17,19, and 20 including SENV (genotypes C and E to G) were not found, presumably due to their low prevalence in the test populations.…”
mentioning
confidence: 94%
“…TTV and TTLVs are widely distributed geographically, with an extremely high prevalence of viremia in the general population, particularly in tropical countries (32) and parts of Asia (6). Mixed-genotype infections are therefore common, particularly in thalassemia patients, due both to the high frequency of viral transmission through repeated therapeutic blood transfusions and the persistent nature of the viruses (5,9,14,15,18,23,31). TTV and TTLVs demonstrate an extremely wide range of sequence divergence.…”
mentioning
confidence: 99%